Udział organizacji społecznej na prawach strony w postępowaniu w sprawie wydania pozwolenia na budowę - Bursztynowicz, Michał (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Under art. 28 paragraph 3 of the Construction Law a social organization cannot take part in the building permit proceedings. Art. 28 paragraph 4 of the Construction Law introduces the exception to this rule, allowing ecological organizations to take part in the proceedings if they require the participation of the community under the act on access to information on the environment and its protection, the community’s participation in the protection of the environment and on environmental impact assessments. The article presents the situations in which a social organization can take part in the building permit proceedings.
Keywords: participation in the building permit proceedings; building permit; ecological organization; environment; social organization